Pengembangan Aplikasi Kriptografi RSA dan SHA-256 Berbasis Web Menggunakan Flask - Nur Azila Tarigan; Anastasya Cut Nabila Anggreni; Alfia Balqis; Indah Nurfadilah; Eri Setia Bakti; Fadli Mahyudin (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
In today's digital era, data security has become a crucial issue due to the increasing volume of information exchanged over the internet. One of the main approaches to protecting data is through the use of cryptographic techniques. This research presents the development of a modern cryptographic application based on web technology, implementing the RSA (Rivest-Shamir-Adleman) algorithm for encryption and decryption processes, as well as the SHA-256 (Secure Hash Algorithm) for generating hash values to verify data integrity. The application is built using the Flask framework and Python programming language, complemented by a responsive interface developed with Bootstrap. Features include the ability to encrypt and decrypt messages, generate hash values, and download keys and processing results in text file formats. The development methodology follows a prototyping approach, with a series of functional tests conducted to ensure encryption accuracy, hashing consistency, and file export reliability. The results show that the application successfully performs all features and provides an intuitive and efficient user experience in understanding basic cryptographic concepts.